Distinct Mitochondrial Pathologies Caused by Mutations of the Proximal Tubular Enzymes EHHADH and GATM - Forst, Anna-Lena; Reichold, Markus; Kleta, Robert; Warth, Richard (Frontiers in Physiology, 2021)
The mitochondria of the proximal tubule are essential for providing energy in this nephron segment, whose ATP generation is almost exclusively oxygen-dependent. In addition, mitochondria are involved in a variety of metabolic processes and complex signaling networks. Proximal tubular mitochondrial dysfunction can therefore affect renal function in very different ways. Two autosomal dominantly inherited forms of renal Fanconi syndrome illustrate how multifaceted mitochondrial pathology can be: Mutation of EHHADH, an enzyme in fatty acid metabolism, results in decreased ATP synthesis and a consecutive transport defect. In contrast, mutations of GATM, an enzyme in the creatine biosynthetic pathway, leave ATP synthesis unaffected but do lead to mitochondrial protein aggregates, inflammasome activation, and renal fibrosis with progressive renal failure. In this review article, the distinct pathophysiological mechanisms of these two diseases are presented, which are examples of the spectrum of proximal tubular mitochondrial diseases.